2014
DOI: 10.1186/1556-276x-9-106
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization reversal in asymmetric trilayer dots: effect of the interlayer magnetostatic coupling

Abstract: The spin structure and magnetization reversal in Co/insulator/Fe trilayer nanodots are investigated by micromagnetic simulations. The vortex and C-state are found and the magnetization reversal is dominated by the shape asymmetry of the dots, which is produced by cutting off a fraction of the circular dot. The vortex chirality is thus controlled by the magnetic field direction. On the other hand, the magnetostatic interaction between the top and bottom magnetic layers has interesting influence on the dot rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The depth of the potential well decreases with the increase in the thickness of the non-magnetic layer. This has been proved in many experiments [36,40]. Increasing the thickness of the Co ring can significantly increase the depth of the potential well, as shown in figure 2(d).…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…The depth of the potential well decreases with the increase in the thickness of the non-magnetic layer. This has been proved in many experiments [36,40]. Increasing the thickness of the Co ring can significantly increase the depth of the potential well, as shown in figure 2(d).…”
Section: Resultsmentioning
confidence: 52%
“…Magnetostatic interaction has been demonstrated for multilayer systems with insulating layers in the middle. The energy does change when the skyrmions move on the multilayer because of the magnetostatic interaction [34,40]. Here, we use one code position to explain the energy potential well in our model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the switching field distribution or SFD of the dot array became broader with a decrease in dot size (figure 9(e)). By performing micromagnetic simulations, Yan et al investigated magnetization reversal in Co/insulator/Fe tri-layer dots with asymmetric shape, where shape anisotropy was induced by slicing away a section of the circular dot [121]. It was found that when the induced shape anisotropy is varied, the reversal field varies significantly owing to the modification of the domain formation process during magnetization reversal.…”
Section: Switching Field Distribution (Sfd) In Magnetic Nanoparticle ...mentioning
confidence: 99%
“…It was observed that the patterning process severely damaged the magnetic layer resulting in a decrease of the switching field and an increase in the switching field distribution (SFD) of the dot array with decreasing dot size (figure 6 (e)). By performing micromagnetic simulations, Yan et al investigated magnetization reversal in Co/insulator/Fe tri-layer dots with asymmetric shape, where shape anisotropy was induced by cutting a section of the circular dot [102].…”
Section: Switching Field Distribution In Magnetic Nanoparticle Arraymentioning
confidence: 99%